2010
DOI: 10.3748/wjg.v16.i23.2913
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bleeding after endoscopic submucosal dissection for gastric lesions

Abstract: Beginner coagulators, tumor in the antrum, and medicines were significant risk factors for post-ESD bleeding. Bleeding at the ulcer margin frequently occurred with beginner operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 11 publications
1
94
7
Order By: Relevance
“…34 Furthermore, 10 studies found no significant differences in elderly patients, 19,25,30,[35][36][37][38][39][40][41] although 1 study identified age > 80 years as an independent risk factor for PPB. 42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB. 24 Arterial hypertension was not identified as a risk factor in most studies, [13][14][15]17,18,[20][21][22][23][24][28]…”
Section: Risk Factors For Ppbmentioning
confidence: 73%
See 3 more Smart Citations
“…34 Furthermore, 10 studies found no significant differences in elderly patients, 19,25,30,[35][36][37][38][39][40][41] although 1 study identified age > 80 years as an independent risk factor for PPB. 42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB. 24 Arterial hypertension was not identified as a risk factor in most studies, [13][14][15]17,18,[20][21][22][23][24][28]…”
Section: Risk Factors For Ppbmentioning
confidence: 73%
“…42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB. 24 Arterial hypertension was not identified as a risk factor in most studies, [13][14][15]17,18,[20][21][22][23][24][28][29][30][31]33,42,43,45 although 2 studies reported significantly higher PPB rates in hypertensive patients. 16,36 However, the adjusted OR was .67 in the latter study.…”
Section: Risk Factors For Ppbmentioning
confidence: 73%
See 2 more Smart Citations
“…In patients for whom the resection was determined to be curative, there was no evidence of local recurrence or distant metastasis during a mean (±SD) observation period of 39.2 ± 25.8 months (range 5.8-91.2 months) in the case of early sESD and 33.3 ± 30.1 months (range 11.9-80.6 months) in the case of late sESD. [25,26]. Here, we analyzed more cases over a longer observation period compared with previous studies, and the total local recurrence rate was 0.4 % (8/2042).…”
Section: Resultsmentioning
confidence: 90%